2016
DOI: 10.2340/00015555-2245
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perception in Primary Cutaneous T-cell Lymphomas: What Patients Believe About Their Disease

Abstract: There is currently no information available on illness perception in primary cutaneous T-cell lymphomas (CTCL). The aim of this study was therefore to gather initial information on disease understanding and interpretation in patients with CTCL. Consecutive patients from a hospital-based primary cutaneous lymphoma ward completed the Revised Illness Perception Questionnaire (IPQ-R) on 2 consecutive visits. A total of 24 patients with different variants of CTCL were included in the study. Patients experienced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
2
22
2
Order By: Relevance
“…Perceiving personal control (over the disease) is associated with better adherence to therapeutic regimens in patients with hypertension (56). Therefore, confidence in managing one's disease might help to improve adherence to treatment by supporting patients' self-control (38). However, the self-administered CTCL-specific questionnaire by Bisaccia et al (27) comprised unique items within its psychological domain compared with Skindex-29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceiving personal control (over the disease) is associated with better adherence to therapeutic regimens in patients with hypertension (56). Therefore, confidence in managing one's disease might help to improve adherence to treatment by supporting patients' self-control (38). However, the self-administered CTCL-specific questionnaire by Bisaccia et al (27) comprised unique items within its psychological domain compared with Skindex-29.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of the relationships between illness perception and HRQoL in CTCL and CBCL were investigated recently (37). The Revised Illness Perception Questionnaire has been shown to assess illness perception reproducibly in CTCL (38). Illness perception reflects patients' individual concepts of understanding and interpretation of the disease (39)(40)(41).…”
Section: Health-related Quality Of Life Questionnaire Outcomes In Cutmentioning
confidence: 99%
“…After, further 189 citations were excluded based on the full-text review, 9 publications were eligible for inclusion. Hand-searching identified an additional 6 relevant publications, resulting in 15 publications which met the predefined inclusion criteria for the HRQoL review [17][18][19]21,22,[37][38][39][40][41][42][43][44][45][46].…”
Section: Study Selectionmentioning
confidence: 99%
“…One study reporting on patients' perspective of their disease was identified [44]. The Revised Illness Perception Questionnaire (IPQ-R) was used to evaluate 22 patients with different variants of CTCL on two consecutive visits to a hospital-based primary cutaneous lymphoma ward [44].…”
Section: Disease Perceptionmentioning
confidence: 99%
“…diabetes, rheumatoid arthritis) and skin (e.g. psoriasis, alopecia, polymorphic light eruption) conditions, but also to address the relationship between beliefs about illness and healthrelated outcomes in various skin diseases (18)(19)(20)(21)(22)(23). This questionnaire consists of three subscales: (i) illness identity scale, (ii) illness perception scales and (iii) causal attributions.…”
Section: Illness Perception Questionnaire-revisedmentioning
confidence: 99%